Investigating the relationships among oral health-related knowledge, attitude, practice, and self-efficacy in predicting oral health behaviors among female Iranian students - Taheri, Akram Mehtari; Hidarnia, Alireza; Zarei, Fatemeh; Tavousi, Mahmoud (Frontiers in Oral Health, 2025)
BackgroundDental caries and other oral health conditions, such as periodontal disease and halitosis, are significant global health issues, particularly among adolescents. Understanding how oral health-related knowledge, attitudes, practices, and self-efficacy contribute to the adoption of preventive oral health behaviors is therefore crucial. This study aimed to investigate the relationships among these factors in predicting oral health behaviors among female Iranian students.MethodsThis cross-sectional analytical study was conducted from April to May 2023 and included 290 seventh-grade adolescent female students from schools in Kashan city. Data were collected via a validated questionnaire measuring knowledge, attitudes, practices, and self-efficacy regarding oral and dental health behaviors. Descriptive statistics, Pearson correlation, and regression analyses were performed via SPSS 24 software.FindingsThe mean ± SD scores for knowledge, attitudes, self-efficacy, and practices were 5.72 ± 1.90, 56.22 ± 6.43, 49.81 ± 12.89, and 26.90 ± 6.28, respectively. Spearman's correlation coefficient revealed a strong relationship between self-efficacy and oral health behaviors (r = 0.657). Regression analysis revealed that self-efficacy was the most significant predictor of oral health behaviors (β = 0.349).ConclusionThe findings indicate that self-efficacy plays a key role in predicting oral health behaviors among adolescent students. Given its strong influence, educational interventions should focus on enhancing self-efficacy alongside improving knowledge, attitudes, and practices to promote better oral health behaviors.